The effects of the human innate pattern recognition receptor L-ficolin and its variants against Hepatitis C virus infection - Mason, Christopher Paul (2019)
Enveloped virus infections have major impacts to global health and economy. For example, Hepatitis C virus is a leading cause of chronic hepatic disease, and the 2013 Ebola virus outbreak highlighted the need for broadly-active treatments. The immune factors behind successful control of these infections are poorly understood. A potential common target for intervention is the glycosylation patterns that decorate the surface proteins of enveloped virions.